2002
DOI: 10.1006/viro.2001.1313
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Organization of the Mamestra configurata Nucleopolyhedrovirus Genome

Abstract: The nucleotide sequence of the genome of the nucleopolyhedrovirus (NPV) from Mamestra configurata (MacoNPV, isolate 90/2), a group II NPV, was determined and analyzed. The MacoNPV DNA genome consists of 155,060 bp and has an overall G+C content of 41.7%. Computer-assisted analysis predicted 169 open reading frames (ORFs) of 150 nucleotides or greater that showed minimal overlap. BLAST searches and comparisons with completely sequenced baculoviruses indicated that there were 66 ORFs conserved among the nine bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 69 publications
9
74
0
2
Order By: Relevance
“…2). This confirms that MacoNPV-A enhancin is expressed as a late gene in the AcMNPV-enMP2 recombinant (Li et al, 2003), and it was translated and incorporated into ODVs as it is in the native MacoNPV-A virus (Fig. 2).…”
Section: Characterization Of Maconpv-a Enhancinsupporting
confidence: 74%
See 3 more Smart Citations
“…2). This confirms that MacoNPV-A enhancin is expressed as a late gene in the AcMNPV-enMP2 recombinant (Li et al, 2003), and it was translated and incorporated into ODVs as it is in the native MacoNPV-A virus (Fig. 2).…”
Section: Characterization Of Maconpv-a Enhancinsupporting
confidence: 74%
“…These studies revealed that betabaculovirus enhancins are associated with OBs . Studies on alphabaculovirus enhancins are limited and relate mostly to LdMNPV (Bischoff & Slavicek, 1997) and MacoNPV-A (Li et al, 2003). These studies revealed that alphabaculovirus enhancins have a transmembrane domain (Bischoff & Slavicek, 1997) and are present in ODV envelopes in association with nucleocapsids (Slavicek & Popham, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AAB47865); LoobMNPV, Lonomia obliqua MNPV (accession no. AAF98122); MacoNPV-A, Mamestra configurata NPV strain 90/2 (Li et al, 2002b); MacoNPV-B, Mamestra configurata NPV strain 96B (Li et al, 2002a); MadiNPV, Malacosoma disstria NPV (accession no. AAD00095); ManeNPV, Malacosoma neustria NPV (accession no.…”
Section: Comparison Of Romnpv and Acmnpv Orfsmentioning
confidence: 99%